First Report of CD4 Lymphopenia and Defective Neutrophil Functions in a Patient with Amebiasis Associated with CMV Reactivation and Severe Bacterial and Fungal Infections - Ghrenassia, Etienne; Guihot, Amélie; Dong, Yuan; Robinet, Pauline; Fontaine, Thierry; Lacombe, Karine; Lescot, Thomas; Meyohas, Marie-Caroline; Elbim, Carole (Frontiers in Microbiology, 2017)
We report the case of a patient with acute necrotizing colitis due to invasive amebiasis associated with CD4 lymphopenia and impaired neutrophil responses. The course of the disease was characterized by CMV reactivation and severe and recurrent bacterial and fungal infections, which might be related to the decreased CD4 T cell count and the impaired functional capacities of neutrophils, respectively. The clinical outcome was positive with normalization of both CD4 cell count and neutrophil functions.